Middle Bronze Age Arsenical Copper Alloys in Southern Portugal. (8th October 2015) - Valério, P.; Soares, A. M. M.; Araújo, M. F.; Silva, R. J. C.; Baptista, L.
Abstract : In the Iberian Peninsula, the copper metallurgy from the Chalcolithic to the Middle Bronze Age (MBA) was mostly characterized by low arsenic contents. A collection of 53 MBA artefacts from southern Portugal was analysed by micro‐EDXRF, optical microscopy, SEM–EDS and Vickers to investigate the metal composition and manufacture. No technological distinction was found between artefacts from domestic and funerary contexts, which were radiocarbon‐dated to 2000–1500 calbc . The arsenic contents of almost 100 MBA artefacts from this region, including the above‐mentioned set, have a Gaussian distribution with a high average (3.9 wt% As). Possible explanations are discussed for this distinctive metallurgy at the south‐western end of the Iberian Peninsula.